The sedimentology of the modern lagoons in the Western Peloponnesus - Kontopoulos, N.; Bouzos, N. (Bulletin of the Geological Society of Greece, 2011)
The Gulfs across of the western Peloponnese are characterized by lagoons. These are located between promontories, in coastal areas where the tidal range is very low. The studied lagoons are very shallow and the sandy mud lithology is the dominant type of the lagoonal bottom sediments. The main hydraulic mechanism for the distribution of the bottom sediments is the winnowing effect by wind action. Further, the studied sediments are characterized as very poorly to extremely poorly sorted and, therefore, the lagoonal environment is one of a very low energy. In this environment the velocity of the depositional agent either fluctuates wide or presents greater consistency. In the bottom sediments, the carbonate and organic material are mostly clastic with an average value of about 35% and 3% respectively. The presence of an abundant clay fraction in the lagoonal sediments allows the precipitation of organic carbon. The latter should be always evaluated when solution to environmental problems is required.